PENERAPAN MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA WORDWALL UNTUK KEMAMPUAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA SMK - Nahda Nadila; Wikanengsih; Yeni Rostikawati (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to determine the effectiveness of student learning through the implementation of the Project Based Learning model assisted by Wordwall media in improving the writing skills of observational report texts among Grade X vocational high school (SMK) students. The research method used is a mixed-methods approach. The design employed in this study is the Exploratory Sequential Design, which combines the sequential collection of qualitative and quantitative data. The population in this study consisted of 27 student. The instruments use include observation sheets, questionnaires, and pretest-posttest assesments to measure the effetiveness of the learning implementation on students’ writing skills in observational report texts. The result of the study indicate a significant improvement in students’ learning outcomes. The findings also show that the implementation of the Project Based Learning model assisted by Wordwall media is effective in enhancing students’ skills in writing observational report texts. This is evident from the posttest scores, which averaged 87, significantly higher than the pretest average of 46. These findings demonstrate that use of the Project Based Learning model assisted by Wordwall media is effective for teaching observational report text writing to avocational high school students.